Critical Study of Ready-Made Garments (RMG) Industry in Bangladesh - Chowdhury, Mohammed Shapan Adnan (2006)
The success of readymade garment exports from Bangladesh over the past two decades has surpassed the most optimistic expectations. This dissertation reviews the literature on this industry, presents recent data on the sector's performance, and evaluates future trends in the international and domestic clothing industry. RMG sector plays a pivotal role in the economy of Bangladesh. There are about 2800 garment factories in the country employing 1.5 million workers. The Study was conducted with the following six aims, which are discussed briefly in the literature review: 1. Production of Textile; 2. Bangladesh Garment Manufacturers and Exporters’ Association (BGMEA); 3. BGMEAs Contribution to the Society and Industry; 4. More contribution of BGMEA; 5. Certain unrest in the Textile Industry in Bangladesh; 6. Some emerging issues in the textile industry in Bangladesh; 7. Competition between Bangladesh and Other Exporting Countries; 8. Assess the Domestic supply for the production; 9. Different setbacks faced in production; 10. Textile Quota removal by WTO, its impact on Bangladesh. The research aims shows that what are the flaws that could be cured to provide better scopes, which would help the industry to grow more widely, and help in the welfare of the country’s economy.